Digital light processing 3D printing of hydrogels: a minireview. Issue 9 (12th July 2022) - Ding, Hongyao; Dong, Min; Zheng, Qiang; Wu, Zi Liang
Abstract : In this review, we give an overview of the recent advances in the field of DLP printing of hydrogels with emphases on materials selection, structure designs, and representative applications. Abstract : The rapid development of three-dimensional (3D) printing of hydrogel materials into sophisticated constructs has led to considerable progress in the fields of tissue engineering, soft actuators/robots, flexible electronics, etc. Notably, digital light processing (DLP) based 3D printing provides a potential strategy to achieve high resolution and elaborate 3D structures that are important for specific applications. In this review, we highlight the recent advances in the field of DLP printing of hydrogels with emphasis on the selection of materials, structure designs, and printing technologies. We then discuss the applications of DLP printed hydrogel constructs in biomedicine, tissue engineering, medical devices, soft actuators, and flexible electronics. Finally, the current challenges and future perspectives of DLP printing of hydrogels are also discussed.